Analisis Penilaian Pelayanan Puskesmas Terhadap Pemberian Vaksin COVID-19 dengan Metode K-Means Clustering - Sriani, Sriani; Suhardi, Suhardi; Damanik, Masliana (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2024)
The Public Health Center is responsible for implementing health policies to achieve health development goals in its area, supporting the realization of a healthy sub-district. One example is the Negeri Lama Public Health Center in Bilah Hilir Sub-district, Labuhanbatu Regency, which serves eight villages with a total population of 36,370 in 2021. The quality of services provided influences patient perceptions, making it essential to continuously improve service quality. This study categorizes the assessment of COVID-19 vaccination services at Negeri Lama Public Health Center using the K-Means Clustering method. This method classifies data into three categories: Very Good Service, Good Service, and Poor Service. The study results show that the Very Good Service category includes six variables with a centroid of 0.519667, the Good Service category includes two variables with a centroid of 0.4605, and the Poor Service category includes two variables with a centroid of 0.3795. This method is considered effective in managing large data accurately